2012
DOI: 10.1186/1471-2334-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a leptospirosis model in guinea pigs using an epicutaneous inoculations route

Abstract: BackgroundLeptospires are presumed to enter their host via small abrasions or breaches of the skin. The intraperitoneal route, although commonly used in guinea pig and hamster models of leptospirosis, does not reflect conditions encountered during natural infection. The aim of this study is to develop a novel leptospirosis guinea pig model through epicutaneous route and to elucidate the pathogenesis of leptospirosis in experimental guinea pigs by comparing the data from other studies using different infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 49 publications
1
28
0
2
Order By: Relevance
“…8 L. interrogans strain Lai did not cause any obvious lesions in C57BL/6 WT mice up to 7 dpi, and this indicated that L. interrogans strain 56606v induced typical acute leptospirosis symptoms in mice in a strain-specific manner.…”
Section: Discussionmentioning
confidence: 88%
“…8 L. interrogans strain Lai did not cause any obvious lesions in C57BL/6 WT mice up to 7 dpi, and this indicated that L. interrogans strain 56606v induced typical acute leptospirosis symptoms in mice in a strain-specific manner.…”
Section: Discussionmentioning
confidence: 88%
“…This popularity has increased the interest in its behavior, physiology and management, leading it to be used as an experimental animal (Taylor & Lee 2012, Dumitrascu et al 2013). Due to anatomical and physiological similarities, related to pregnancy and placentation (Miglino et al 2004, Mess 2007, Vasconcelos et al 2013, this species became extremely important as an experimental model for human placentation, as well as for respiratory diseases (Canning & Chou 2008, Skerry et al 2013), cardiovascular problems (Zaragoza et al 2011), and bacterial, viral and fungal infections (Pica et al 2012, Zhang et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…First, leptospirosis is assumed to cause systemic vasculitis, which could be an important mechanism of tissue damage and hemorrhagic tendencies . Inflammation of the vascular endothelium may be a consequence of direct invasion by infectious agents or of immune mechanisms . Second, thrombocytopenia is a well‐documented feature of leptospirosis (14–58% in naturally occurring leptospirosis in dogs) .…”
mentioning
confidence: 99%